CONTROL SYSTEM DESIGN OF FLYWHEEL ANGLE POSITION WITH MOTOR DC DRIVE - Aziz Sasono, Fahmi
To improve student’s understanding about the application of the Introduction to Control System course given, the Mechanical Engineering Study Program FTMD, ITB has provided course with experiment laboratory activity. Unfortunately, the current activity cannot show the instability phenomenon of a dynamic system. Therefore, this project aims to build a position control test rig capable of showing instability phenomenon visually. The position control system developed in this final project uses a direct current motor with an internal gear connected to a flywheel. To drive the motor, an analog signal power amplifier is built based on a push-pull transistor circuit with emitter follower. In the system, the position of the flywheel shaft angle is measured using a potentiometer that is connected at the shaft. The power amplifier has a static gain that is arranged so that the power amplifier and output is compatible with NI 6000 series input that are used previously. In this project, the control algorithm used is a PI controller so that the steady-state error due to friction can be eliminated. The results of the analysis and testing conducted show that, the test rig developed capable of showing the instability phenomenon visually when the system stability requirements are violated. In, this project, PI parameters suitable for the system was also proposed based on a phase margin analysis.